Pediatric acute-onset neuropsychiatric syndromes and the gut-oral-brain axis: a narrative review of emerging microbiome-immune interactions and therapeutic perspectives - Matera, Mariarosaria; Biagioli, Valentina; Illiceto, Maria Teresa; Palazzi, Chiara Maria; Cavecchia, Ilaria; Manzi, Andrea; Lugli, Sebastian; Pennazzi, Laura; Meocci, Martina; Pedaci, Fausto Andrea; Bertuccioli, Alexander (Frontiers in Immunology, 2025)
BackgroundPediatric Acute-onset Neuropsychiatric Syndromes (PANS) and Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal infections (PANDAS) are characterized by sudden-onset neuropsychiatric symptoms. Growing evidence indicates that gut and oral microbiota may contribute to disease pathogenesis through immune and inflammatory pathways.MethodsThis narrative review analyzed approximately 250 studies published between 2000 and 2024, retrieved from PubMed, Scopus, and Google Scholar. The selected works included clinical, immunological, and microbiome-related studies investigating the role of gut–oral–brain interactions in neuroinflammation or in pediatric PANS/PANDAS.FindingsAlterations in gut and oral microbial communities appear to modulate neuroinflammation through increased intestinal and blood–brain barrier permeability, immune dysregulation, and altered production of neuroactive metabolites. Specific bacterial families, such as Bacteroidaceae, Rikenellaceae, and Odoribacteriaceae, have been associated with pro-inflammatory states, while oral pathogens may exacerbate systemic inflammation via the gut–oral–brain axis.ConclusionsThe reviewed evidence highlights the potential of microbiome-targeted strategies—including dietary modulation, probiotics, and anti-inflammatory approaches—as promising avenues for future personalized diagnosis and therapy in PANS/PANDAS. However, further controlled studies integrating microbial, immunological, and clinical data are required to confirm causal mechanisms and establish personalized therapeutic protocols.